Vicinal ketoesters – key intermediates in the total synthesis of natural products - Beller, Marc Paul; Koert, Ulrich (Beilstein Journal of Organic Chemistry, 2022)
This review summarizes examples for the application of vicinal ketoesters such as α-ketoesters, mesoxalic esters, and α,β-diketoesters as key intermediates in the total synthesis of natural products utilizing their electrophilic keto group as reactive site. Suitable key reactions are, e.g., aldol additions, carbonyl ene reactions, Mannich reactions, and additions of organometallic reagents. The vicinal arrangement of carbonyl groups allows the stabilization of reactive conformations by chelation or dipole control.
Keywords: aldol addition; ketoesters; natural products; total synthesis